Mutation induction in sweet basil (Ocimum basilicum L.) by fast neutron irradiation - Enkhbileg, E.; Fenyvesi, A.; Bíró, B.; Fári, M. G.; Kurucz, E. (International Journal of Horticultural Science, 2019)
Basil species are highly sensitive to exterior environmental conditions and its consequences lead to great economic and agronomic losses. In this research, a mutation method was optimized out for creating a new variety of Ocimum basilicum L., which could tolerate the extreme/extraordinary climatic circumstances or biotic stresses, such as fungal diseases. Fast neutron irradiation was performed on the Hungarian commercial variety seeds with doses of 5 to 60 Gray and grown into fully developed plants. Numerous phenotypical changes like deformed congestion, leaf mutation, and low growth occurred, especially at higher dosages. Then to confirm whether the plantlets had mutation or not, and to detect the molecular variation and relationship, fingerprinting profiles of the developed mutant regenerants and donor plant have been assessed using ISSR markers. 115 loci were yielded, ranging from 0.2 to 1.5 kb, out of which 110 loci were polymorphic in nature, representing 95.6% polymorphism. The most suitable primer to determine the genetic diversity within the Ocimum species was the UBC-856 with 0.42 PIC and 4.1 MI values.